2008
DOI: 10.1371/journal.pone.0001928
|View full text |Cite
|
Sign up to set email alerts
|

Oral High-Dose Atorvastatin Treatment in Relapsing-Remitting Multiple Sclerosis

Abstract: BackgroundRecent data from animal models of multiple sclerosis (MS) and from a pilot study indicated a possible beneficial impact of statins on MS.Methodology/Principal FindingsSafety, tolerability and effects on disease activity of atorvastatin given alone or in combination with interferon-beta (IFN-β) were assessed in a phase II open-label baseline-to-treatment trial in relapsing-remitting MS (RRMS). Patients with at least one gadolinium-enhancing lesion (CEL) at screening by magnetic resonance imaging (MRI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(83 citation statements)
references
References 19 publications
4
73
4
Order By: Relevance
“…However, results of recent studies with combined therapy with IFN-b and statins are controversial. Both beneficial and harmful results of combined therapy were reported (Birnbaum et al 2008;Paul et al 2008;Rudick et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…However, results of recent studies with combined therapy with IFN-b and statins are controversial. Both beneficial and harmful results of combined therapy were reported (Birnbaum et al 2008;Paul et al 2008;Rudick et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Encouraging results from studies on the effect of statins in the experimental animal models for MS have instigated the evaluation of statins as (co)therapy in MS (Paintlia et al, 2008;Paintlia et al, 2009;Stanislaus et al, 1999;Youssef et al, 2002). Although initial studies have indicated that statins are safe for use in MS (Lanzillo et al, 2010;Paul et al, 2008;Togha et al, 2010;Vollmer et al, 2004), the effects on the disease course are still unclear. Preliminary studies have reported positive effects of statins in relapsing remitting (RR)MS when administered as monotherapy, as well as cotherapy in combination with IFN-b (Paul et al, 2008;Togha et al, 2010;Vollmer et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Although initial studies have indicated that statins are safe for use in MS (Lanzillo et al, 2010;Paul et al, 2008;Togha et al, 2010;Vollmer et al, 2004), the effects on the disease course are still unclear. Preliminary studies have reported positive effects of statins in relapsing remitting (RR)MS when administered as monotherapy, as well as cotherapy in combination with IFN-b (Paul et al, 2008;Togha et al, 2010;Vollmer et al, 2004). By contrast, the use of high doses of ATOR in combination with IFN-b has been shown to negatively influence disease course in RRMS patients, resulting in new and enhanced lesions (Birnbaum et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43][44] Overall, further studies regarding adjuvant statin and disease-modifying therapy are needed to better understand their role in MS disease activity and progression.…”
Section: Dyslipidemiamentioning
confidence: 99%